Coffee seed storage (Research, Society and Development, 2022)
Coffee seeds quickly lose viability during storage, which makes it a major problem for producers to maintain their physiological quality until the right time for sowing. In this research, the performance of coffee seeds stored under different environmental conditions and types of packaging was investigated. For this purpose, coffee seeds were used, cultivar Catuaí Amarelo, harvested in the 2019 harvest, at Fazenda Bom Jardim, municipality of Bom Sucesso - MG. Then, the seeds were packed in permeable and impermeable packages, for a period of six months, in two environments: 15 ° C and 25 ° C. Before storage, the seeds were evaluated by the germination test, emergence speed index and tetrazolium test. It can be concluded that regardless of the storage location, coffee seeds lose viability over the months. In cold chamber conditions it is possible to store for up to 4 months without the seeds suffering so much, but with a lower germination rate.